The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/s0004-2803.202100000-56
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Lead and Cadmium Levels in Blood and Refractory Chronic Constipation Among Iranian Children

Abstract: BACKGROUND: There is limited research examining reasons causing refractory chronic constipation (RCC) in children. The effects of lead (Pb) and cadmium (Cd) exposures on this condition have been even less clear. However, some related factors may contribute to evaluation of blood lead levels (BLLs) and blood cadmium levels (BCLs). OBJECTIVE: The present study aimed to examine the relationship between Pb and Cd exposures and RCC in children living in the city of Ahvaz, Khuzestan Province, in Southwestern Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Several previous cases (Wu et al 2013;Ying et al 2016) have reported that lead intoxication can lead to constipation. However, a recent study (Gharibshahi et al 2021) found that lead exposure due to environmental pollution and susceptibility to heavy metals might not be associated with refractory chronic constipation in children. In our current study, we observed an inverse association between the blood levels of lead and chronic constipation.…”
Section: Discussionmentioning
confidence: 96%
“…Several previous cases (Wu et al 2013;Ying et al 2016) have reported that lead intoxication can lead to constipation. However, a recent study (Gharibshahi et al 2021) found that lead exposure due to environmental pollution and susceptibility to heavy metals might not be associated with refractory chronic constipation in children. In our current study, we observed an inverse association between the blood levels of lead and chronic constipation.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic inhalation exposure to cadmium particles is linked to pulmonary function abnormalities and chest radiographs that are suggestive of emphysema [78]. Cigarette smokers have greater blood and urine cadmium levels, while former smokers have intermediate levels and nonsmokers have lower levels [79]. High quantities of chromium(VI) in the air might irritate the lining of the nose and cause ulcers.…”
Section: Effect Of Heavy Metals On Humanmentioning
confidence: 99%